2023
DOI: 10.1128/spectrum.03664-22
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Qingyi Decoction in Severe Acute Pancreatitis-Associated Acute Lung Injury via Gut Microbiota: Targeting the Short-Chain Fatty Acids-Mediated AMPK/NF-κB/NLRP3 Pathway

Abstract: Gut microbiota affects the severity of SAP-ALI and intestinal barrier function. During SAP, a significant increase in the relative abundance of gut pathogens ( Escherichia , Enterococcus , Enterobacter , Peptostreptococcus , Helicobacter ) was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…SCFAs also play an important role in the immune response of the host and in metabolism. Numerous studies have shown that the gut microbiota can modulate SCFAs to alleviate acute lung injury [54][55][56]. In the present study, heat-inactivated MRSA induced a decrease in SCFAs in ALI in mice, and propolis pretreatment elevated the concentrations of acetic acid and valeric acid to reverse these changes.…”
Section: Discussionsupporting
confidence: 47%
“…SCFAs also play an important role in the immune response of the host and in metabolism. Numerous studies have shown that the gut microbiota can modulate SCFAs to alleviate acute lung injury [54][55][56]. In the present study, heat-inactivated MRSA induced a decrease in SCFAs in ALI in mice, and propolis pretreatment elevated the concentrations of acetic acid and valeric acid to reverse these changes.…”
Section: Discussionsupporting
confidence: 47%
“…Substantial research has supported that the gut microbiota is closely related to the development and progression of ALI by transmitting gut-lung axis activation. The intestinal flora plays an important role in maintaining the normal immune function of the body, reducing bacterial translocation and improving lung injury [48]. Compared to the control group, the model group with an imbalance in the gut flora showed more obvious gut damage and decreased expression of ZO-1 and occludin [29,49].…”
Section: Discussionmentioning
confidence: 99%
“…To the extent of our knowledges, our research constitutes the first wide-ranging, in-depth MR analysis aimed at examining the cause-and-effect relationship between intestinal microbiota and pancreatitis at a genetic prediction scale. Prior research probing the relationship between gut microbiota and pancreatitis has predominantly utilized animal models as the primary mode of investigation (Zhang et al, 2019;Zhu et al, 2019;Glaubitz et al, 2023;Hu et al, 2023;Jiao et al, 2023;Wang Z. et al, 2023). These findings might bear significance for public health initiatives that are targeted toward mitigating the risk associated with pancreatitis.…”
Section: Discussionmentioning
confidence: 99%